Public health risks associated with food‐borne parasites. (4th December 2018) - ,; Koutsoumanis, Kostas; Allende, Ana; Alvarez‐Ordóñez, Avelino; Bolton, Declan; Bover‐Cid, Sara; Chemaly, Marianne; Davies, Robert; De Cesare, Alessandra; Herman, Lieve; Hilbert, Friederike; Lindqvist, Roland; et al.
Abstract: Parasites are important food‐borne pathogens. Their complex lifecycles, varied transmission routes, and prolonged periods between infection and symptoms mean that the public health burden and relative importance of different transmission routes are often difficult to assess. Furthermore, there are challenges in detection and diagnostics, and variations in reporting. A Europe‐focused ranking exercise, using multicriteria decision analysis, identified potentially food‐borne parasites of importance, and that are currently not routinely controlled in food. These are Cryptosporidium spp., Toxoplasma gondii and Echinococcus spp. Infection with these parasites in humans and animals, or their occurrence in food, is not notifiable in all Member States. This Opinion reviews current methods for detection, identification and tracing of these parasites in relevant foods, reviews literature on food‐borne pathways, examines information on their occurrence and persistence in foods, and investigates possible control measures along the food chain. The differences between these three parasites are substantial, but for all there is a paucity of well‐established, standardised, validated methods that can be applied across the range of relevant foods. Furthermore, the prolonged period between infection and clinical symptoms (from several days for Cryptosporidium to years for Echinococcus spp.) means that source attribution studies are very difficult. Nevertheless, our knowledge of the domestic animal lifecycle (involving dogs and livestock) for Echinoccocus granulosus means that this parasite is controllable. For Echinococcus multilocularis, for which the lifecycle involves wildlife (foxes and rodents), control would be expensive and complicated, but could be achieved in targeted areas with sufficient commitment and resources. Quantitative risk assessments have been described for Toxoplasma in meat. However, for T. gondii and Cryptosporidium as faecal contaminants, development of validated detection methods, including survival/infectivity assays and consensus molecular typing protocols, are required for the development of quantitative risk assessments and efficient control measures.